1233 Can speckle tracking echocardiography predict outcome in hypoplastic left heart syndrome patients?. (17th January 2020) - Borrelli, N S; Di Salvo, G; Sabatino, J; Ibrahim, A; Avesani, M; Filippini, E; Josen, M; Penco, M; Fraisse, A; Michielon, G
Abstract: Funding Acknowledgements: EACVI Training Grant Introduction: Children with Hypoplastic Left Heart Syndrome (HLHS) have a high mortality (up to 95%) and morbidity. Systemic right ventricle (RV) dysfunction plays a key-role in their outcome. Purpose: The aim of this study is to evaluate the accuracy of speckle-tracking echocardiographic (STE) assessment of RV deformation and 2D standard echo parameters in predicting death and need for heart transplantation (HT) in HLHS patients. Methods: 31 patients with diagnosis of HLHS successfully completed Norwood (n = 29) or comprehensive Norwood stage II (n = 2) at our Institution between 2015 and 2019. Survival at 6 months was 90.32%, survival at 18 months was 85.72%. We studied 29 HLHS patients (17 male). Patients with HLHS variant (n = 2) were excluded. All the studied patients underwent in-hospital interstage stay. Serial echocardiographic assessment was performed in all the included patients (baseline, one month after Norwood, three months after Norwood, one week before bidirectional cavopulmonary anastomosis [BCPA] and two months after BCPA). From the apical view we measured: tricuspid annulus peak systolic excursion (TAPSE), fractional area change (FAC), longitudinal strain (LS) and strain rate (LSR). Results: After a mean follow-up of 1.83 ± 1.16 years, 8 out of 29 of the included patients met the composite endpoint of death/HT. At pre-Norwood assessment, there was no statistical difference in echo measurements between survivors and patients who reached the endpoint. In death/HT group TAPSE and LS declined already at one-month after Norwood procedure evaluation. At one-month evaluation, a TAPSE ≤ 5 mm had a good sensitivity for death/HT (85.71%) and a moderate specificity (66.67%), with an area under the curve of 0.789. Always at one-month evaluation, a Δ LS ([baseline LS – one-month post Norwood LS/ baseline LS] *100) of 8.7% showed a 100% sensitivity and good specificity (80.95%) for death/HT, with an area under the curve of 0.888. Multivariate analysis showed that one-month-after-Norwood Δ LS was the best predictor of worse outcome (p = 0.02). Conclusions: HLHS patients with Δ LS of > 8.7% at one-month after Norwood procedure had a high likelihood of death or HT. These data encourage the routine use of LS to monitor cardiac function in HLHS patients.